2011
DOI: 10.1111/j.1742-4658.2011.08188.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of translational efficiency by different splice variants of the Disc large 1 oncosuppressor 5′‐UTR

Abstract: Human Disc large (DLG1) has been demonstrated to be involved in the control of cell polarity and maintenance of tissue architecture, and is frequently lost in human tumours. However, the mechanisms controlling DLG1 expression are poorly understood. To further examine the regulation of DLG1 expression, we analysed the 5′ ends of DLG1 transcripts by rapid amplification of cDNA ends polymerase chain reaction. We identified an alternative splicing event in the 5′ region of DLG1 mRNA that generates transcripts with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 47 publications
(71 reference statements)
1
19
0
Order By: Relevance
“…Moreover, we identified the presence of an alternative splicing event in the 5′-UTR of DLG1 that generates two different transcripts: the short and large variants ( Figure 1A). The exclusion of the alternative spliced exon in the short form increases the efficiency of DLG 1 translation, indicating the participation of the 5′-UTR in the control of DLG1 abundance (Cavatorta et al, 2011). We showed that this event is significant in the regulation of DLG1 levels in transformed cells, in agreement with the concept that many oncogenes and tumour suppressor genes express complex 5′-UTRs that participate during carcinogenesis.…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations
“…Moreover, we identified the presence of an alternative splicing event in the 5′-UTR of DLG1 that generates two different transcripts: the short and large variants ( Figure 1A). The exclusion of the alternative spliced exon in the short form increases the efficiency of DLG 1 translation, indicating the participation of the 5′-UTR in the control of DLG1 abundance (Cavatorta et al, 2011). We showed that this event is significant in the regulation of DLG1 levels in transformed cells, in agreement with the concept that many oncogenes and tumour suppressor genes express complex 5′-UTRs that participate during carcinogenesis.…”
Section: Introductionsupporting
confidence: 66%
“…The alternative DLG1 5′-UTRs are expressed in cell lines from different tissues Our previous analyses of DLG1 expression were mainly focused on epithelial cells (Cavatorta et al, 2011). However, this protein was shown to be expressed in several tissues (Lue et al, 1994) and many reports indicate that DLG1 is also involved in many activities in cells such as lymphocytes and neurons.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…These domains include three PSD-95/Dlg/ZO-1 (PDZ) domains, an SH3 domain and a catalytically inactive guanylate kinase (GUK) domain common to all membrane-associated GUK (MAGUK) scaffolds, as well as an L27 oligomerization domain, an N-terminal proline rich region and a C-terminal HOOK domain, which are unique to Dlg1. Dlg1 domain structure can be modified by alternative splicing events that are thought to effect Dlg1 stability, localization and function (10)(11)(12)(13)(14)(15).…”
Section: P Roper Activation Of Cd8mentioning
confidence: 99%